2020
DOI: 10.3892/mmr.2020.11354
|View full text |Cite
|
Sign up to set email alerts
|

Mannose shows antitumour properties against lung cancer via inhibiting proliferation, promoting cisplatin‑mediated apoptosis and reducing metastasis

Abstract: it has been reported that mannose exerts antitumour effects against certain types of cancer. The present study was designed to evaluate whether mannose exerted potential anticancer effects on a549 and H1299 non-small cell lung cancer (nSclc) cells in vitro, which has not been reported previously. a cell counting Kit-8 cell viability assay was used to assess the antiproliferative effects of mannose on nSclc cells. Flow cytometry-based methods were used to evaluate the effects of mannose on the cell cycle distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Of note, a recent study has shown that the mannose uptake by a panel of cancer cells following millimolar mannose supplementation leads to the accumulation of M6P, which subsequently impairs glucose flux into central carbon metabolism and inhibits cancer growth [ 132 ]. In a similar vein, mannose supplementation was also shown to have an anticancer effect in non-small cell lung cancer (NSCLC) cells through inhibiting proliferation and increasing cell death [ 133 ]. Translating these recent findings into the antineoplastic role of mannose may lead to a novel route of treatment for cancer and improved outcomes for cancer patients.…”
Section: Mannose Metabolism Disordersmentioning
confidence: 99%
“…Of note, a recent study has shown that the mannose uptake by a panel of cancer cells following millimolar mannose supplementation leads to the accumulation of M6P, which subsequently impairs glucose flux into central carbon metabolism and inhibits cancer growth [ 132 ]. In a similar vein, mannose supplementation was also shown to have an anticancer effect in non-small cell lung cancer (NSCLC) cells through inhibiting proliferation and increasing cell death [ 133 ]. Translating these recent findings into the antineoplastic role of mannose may lead to a novel route of treatment for cancer and improved outcomes for cancer patients.…”
Section: Mannose Metabolism Disordersmentioning
confidence: 99%
“…These variations can be attributed to fructose‐mediated alterations in glycosylation structures, which have been associated with aggressive and metastatic phenotypes [ 66 ]. By contrast, mannose uptake by cancer cells impedes glucose flux into central carbon metabolism pathways, inhibiting cancer cell proliferation [ 67 ], and a recent study revealed that mannose supplementation has anticancer effects in NSCLC cells, inhibiting proliferation and increasing cell death [ 68 ]. The most important upregulated functional metabolites were related to metabolic pathways involved in energy metabolism and cell proliferation, such as glycerophospholipid metabolism, which had the highest impact score among the pathways associated with the stroma classifier.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Recently, mannose was reported to be effective against lung cancer, breast cancer, and osteosarcoma. 28 , 29 , 30 , 31 , 32 Low expression of PMI makes cells more sensitive to the antitumor effect of mannose, and all of these cancers express low levels of PMI. By contrast, leukemia cells express PMI, but it remains unclear how mannose metabolism contributes to their survival and proliferation.…”
Section: Discussionmentioning
confidence: 99%